Analyzing Factors Influencing Commuter Behavior in Jabodetabek through Factor Analysis - Wulan Asti Rahayu; Utomo Sarjono Putro; Pri Hermawan; Yos Sunitiyoso (Research Synergy Foundation, 2023)
Public transportation is vital for addressing urban mobility challenges and reducing traffic congestion. Understanding commuter behaviour, attitudes, and preferences is crucial to improving public transportation systems and encouraging usage. This research aims to identify commuter segments based on demographics, attitudes, and behaviours, and to determine their future intentions towards public transportation. An online survey collected data from 257 respondents residing in the Greater Jakarta area, encompassing Jakarta, Bogor, Depok, Tangerang, and Bekasi. Segmentation was achieved using factor analysis. However, they had significant health concerns, especially during the COVID-19 pandemic. Surprisingly, all three segments demonstrated similar future intentions regarding public transportation use post-pandemic, posing governance challenges for promoting public transportation and integrating transport systems in Jabodetabek. These facets included a positive perception of public transit, an intent to pivot transportation modes influenced by factors such as risk, cost, and comfort, and heightened health apprehensions about using public transportation during the COVID-19 pandemic. While invaluable for policymakers seeking tailored interventions for different commuter segments, these insights come with a caveat: the primary focus on Greater Jakarta might limit the broader applicability of the findings. Therefore, policymakers and researchers should approach the results with discernment, especially when considering their implications in other urban contexts.